A Space of their Own: Representing Migrant Experience in In the Skin of a Lion and Me Migrant - Yew, Andrea (SARE: Southeast Asian Review of English, 2017)
The representation of migrant experience is fraught with challenges. Not only is the writer increasingly forced into restrictive narratives, which are founded upon reductive assumptions of the migrant subject, in some cases, he or she also has to transcend the barriers of writing in a language that is not their characters’ mother tongue. This paper aims to examine the ways in which Michael Ondaatje and Md Mukul Hossine tackle these issues and expand upon the representation of migrant experience by challenging existing grand narratives. It also examines the way in which both writers reconfigure narrative spaces through the use of metaphors in their attempt to represent the peculiarities of migrant experience. Adding to their challenge is that migrant experience is often characterized by a trauma that inherently resists representation. This, coupled with the fact that any representation of migration has to grapple with the politics of language, can pose problems of accessibility. This paper considers how both writers negotiate these difficulties, arguing that both Ondaatje and Hossine ultimately transcend language in order to convey the distinctive contours of migrant experience.